Analytical marketing - Simon, Leonard S. (Harcourt, Brace & World, 1970)
This book stems from a latent need we perceived in our joint research work. During our construction of analytical models for various decision problems in marketing, the question arose as to whether the type of output we were producing would be taught to students specializing in marketing.